Statistical study on the degree of satisfaction of patients with fixed prosthetic dentures - Crăciun Adriana-Elena; Cerghizan Diana; Baloș Monica Dora; Gribincea Vadim; Albu Aurița Ioana; Muică Adrian (Acta Stomatologica Marisiensis, 2019)
Introduction: Edentation is a major emergency and has an echo over the entire stomatognathic system. The treatment of partial edentation has undergone major changes in the last decades for multiple causes, including increasing the level of dental, medical education, introducing new techniques, methods, and materials, increasing the duration of retention of teeth on the arch.